Emotional Dependence, Satisfaction with Life and Partner Violence in University Students - Ponce-Díaz, Carlos (2019)
The objective of the study was to analyze the relationship between emotional dependence and satisfaction with life in a group of Psychology students from public and private universities in Metropolitan Lima, victims and non-victims of partner violence. The research involved 1211 university students with an average age of 21.7 years (SD = 4.7), 54% not subjected to  any partner violence and 46%  who had experienced violence. The instruments used were the Questionnaire on Violence between partners (CUVINO, Rodríguez-Franco et al., 2010), the Inventory of Emotional Dependence (IDE, Aiquipa, 2015) and the Satisfaction with Life Scale (SWLS, Diener, Emmons, Larsen & Griffin, 1985). The results indicate that in the group of women experiencing  partner violence there is a statistically significant relationship and an inverse relationship between emotional dependence and life satisfaction, both for the total scale (-0.24, p <.005) and for all dimensions (values between -0.128 to -0.26, p <.001). However, in the group of women not subjected to partner violence, the relationship between the study variables was lower (-0.11, p <.005) and some relationship was only found between satisfaction with life and three of the seven dimensions (values between -0.11 to -0.16, p <.005).